Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.21203/rs.3.rs-67563/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Do Laboratory Biomarkers Predict Survival in Severe COVID-19? A Cross-sectional Study

Abstract: BackgroundAvailable research compared serum biomarkers such as lymphocyte count, C-reactive protein, ferritin, Lactate Dehydrogenase and D-dimers to predict survival in patients with mild, moderate and severe COVID-19. This study aims to compare these biomarkers among survivors and non-survivors of severe COVID-19. MethodsThis was a cross-sectional study based on patient’s data retrieved from Hospital Information System. Sixty-nine patients for whom a record of the biomarkers and survival status was available,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…Another similar study compared these markers among survivors and non-survivors showed that lymphocyte count decreased significantly in both survivors (from 0.94 to 0.51 × 10 9 cells/L) and non-survivors (from 1.24 to 0.61 × 10 9 cells/L), respectively. Among survivors, the increase in CRP level was from 158.0 to 178.7 mg/L while among nonsurvivors, the increase in CRP level was from 166.8 to 207.7 mg/L [17]. There was an equal rise in serum ferritin among the survivors (1321.13 to 2141.18 ng/mL) and non-survivors (1227.01 to 1662.7 ng/mL).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Another similar study compared these markers among survivors and non-survivors showed that lymphocyte count decreased significantly in both survivors (from 0.94 to 0.51 × 10 9 cells/L) and non-survivors (from 1.24 to 0.61 × 10 9 cells/L), respectively. Among survivors, the increase in CRP level was from 158.0 to 178.7 mg/L while among nonsurvivors, the increase in CRP level was from 166.8 to 207.7 mg/L [17]. There was an equal rise in serum ferritin among the survivors (1321.13 to 2141.18 ng/mL) and non-survivors (1227.01 to 1662.7 ng/mL).…”
Section: Discussionmentioning
confidence: 85%
“…The rise in serum LDH levels in survivors was 829.59 to 1018.6 U/L while in nonsurvivors it was 816.2 to 1056.61 U/L. D-dimer levels increased significantly in both survivors and non-survivors (from 7.2 to 28.8 µg/mL, and from 8.75 to 29.52 µg/mL, respectively) [17]. Similarly, another study concluded peak D-dimer levels of 42.2 µg/ml on day 22 of admission in non-survivors, peak lymphocytopenia on day 7 for survivors (0.91 x 10 9 cells/L), and day 22 for nonsurviving patients (0.42 x 10 9 cells/L).…”
Section: Discussionmentioning
confidence: 89%